2006
DOI: 10.1007/s10750-005-1132-2
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal and Spatial Patterns of Distribution of Subtidal Benthic Invertebrate Communities in the Mondego River, Portugal – A Poikilohaline Estuary

Abstract: The use of benthic assemblages to assess ecological quality of estuarine environments is a major tool for the implementation of the Water Framework Directive (2000/60/CE) for European aquatic ecosystems. Benthic communities show spatially heterogeneous distributions and experience seasonal variations due to both natural and anthropogenic stresses. The major goal of this study was to quantify the relationships between environmental gradients and the spatial and temporal patterns of the benthic communities along… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
28
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(28 citation statements)
references
References 32 publications
0
28
0
Order By: Relevance
“…Winter and spring were the wettest seasons compared to summer, which was generally drier. This follows the pattern of most temperate estuaries, and is characterised by having a significant influx of freshwater during the winter, which has an impact on salinity variation (Elliott & McLusky 2002;Chainho et al 2006;Teixeira et al 2008). The presence of gravel at upstream stations and the accumulation of muddy sediments in the stations near of mouth of Cávado estuary detected in the present study has also been observed in other Portuguese estuaries Chainho et al 2007;Sousa et al 2008b;Teixeira et al 2008).…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…Winter and spring were the wettest seasons compared to summer, which was generally drier. This follows the pattern of most temperate estuaries, and is characterised by having a significant influx of freshwater during the winter, which has an impact on salinity variation (Elliott & McLusky 2002;Chainho et al 2006;Teixeira et al 2008). The presence of gravel at upstream stations and the accumulation of muddy sediments in the stations near of mouth of Cávado estuary detected in the present study has also been observed in other Portuguese estuaries Chainho et al 2007;Sousa et al 2008b;Teixeira et al 2008).…”
Section: Discussionmentioning
confidence: 83%
“…The sediment type was also important in spatial distribution of epibenthic communities, being the abundance, biomass and the diversity indexes better correlated with the presence of fine sediment (<0.125mm). The differences found were expected since the hydrodynamic fluctuations have an important effect on the cycles of sediment erosion and deposition and, hence, on the colonisation of benthic communities (Chainho et al 2006).…”
Section: Tabela 4 Combinação Das Variáveis (K) Que Fornecem Os Valormentioning
confidence: 84%
“…The response of an estuary to these events can reveal a great deal about its resilience and the role of disturbance in shaping its structure and function (Davis et al, 2004). In addition, an understanding of the effects of natural events on estuarine organisms is a basic tool in discriminating between natural changes and human disturbances (Chainho et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…However, less is understood about their effects in estuaries (Matthews & Constable, 2004). The use of benthic invertebrate assemblages to monitor the ecological quality of estuaries is a major tool in the implementation of the Water Framework Directive (2000/60/CE) but it is vital to identify the impact of extreme natural events so that they can be discriminated from human impacts (Chainho et al, 2006). It was predicted that the high flow events would cause changes in the diversity of the associated epi-and in-fauna of the estuarine mussel beds due to mortality of more sensitive species, colonisation by opportunistic species and/or physical transportation of species from further up the estuary (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Many studies have investigated the distribution (Chainho et al, 2006;Rodrigues et al, 2006), abundance Dittman, 2002b), diversity (Boehs et al, 2004) and biomass (Masero et al, 1999;Silva et al, 2006) of invertebrates on intertidal flats. There have also been many studies that examine the effect of environmental variables on invertebrate abundance and community composition (Anderson, 1972;Castel et al, 1989;Edgar & Barrett, 2002).…”
Section: Introductionmentioning
confidence: 99%